Samoregulacja działalności gospodarczej i zawodowej : organizacje samoregulacyjne w prawie rosyjskim - Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Self-regulation of economic and professional activity consists of creating and controlling the observance of norms regulating a given activity by entities performing this activity. In Russian law, self-regulation is carried out primarily through the functioning of self-regulatory organizations, associating entities of specific economic or professional activity. Self-regulatory organizations function as voluntary and mandatory membership organizations. In certain areas of economic and professional activity, obtaining membership in a self-regulatory organization, subject to the fulfillment of certain conditions is a legal requirement to undertake a given activity. For this reason, self-regulatory organizations with mandatory membership should be considered public law corporations. The public-law nature of these organizations is transcendent due to the bottom-up way of their creation.
Keywords: economic activity; professional activity; self-regulation; self-regulatory organization; Russian law